Forzzaea bahiana (Bromeliaceae: Bromelioideae): a new species from the Caatinga of northeastern Brazil - Engels, Mathias Erich; Smidt, Eric De Camargo; Leme, Elton M. C. (Phytotaxa, 2023)
We describe and illustrate Forzzaea bahiana, a new bromeliad species that grows as a saxicole on flat rocky outcrops in the northwest of Chapada Diamantina, Bahia State, greatly extending the geographical distribution of the genus to the Septentrional Plateau of the Espinhaço range, in northeastern Brazil. The new species is morphologically related to Forzzaea micra and can be differentiated mainly by the sepals with an irregularly serrate margins, sepals and petals with glandular trichomes on the abaxial surface, broader petals with entire margins, smaller anthers, and by the simple-patent stigma type.